Blondie 24 : - Fogel, David B. (Morgan Kaufmann Publishers, 2002)
Blondie24 tells the story of a computer that taught itself to play checkers far better than its creators ever could by using a program that emulated the basic principles of Darwinian evolution--random variation and natural selection-- to discover on its own how to excel at the game.